Alkaline pH shock enhanced production of validamycin A in fermentation of Streptomyces hygroscopicus. (February 2018) - Jiang, Jing; Sun, Ya-Fang; Tang, Xi; He, Chao-Nan; Shao, Ye-Lin; Tang, Ya-Jie; Zhou, Wen-Wen
Highlights: A valuable and optimal pH shock strategy for Val-A fermentation was reported. Alkaline pH shock significantly increased Val-A production by 27.43%. Respiratory activity and amino acid metabolism were crucial in pH shock treatment. Effect mechanism based on genes, microenvironments and metabolites was explored. Abstract: Validamycin A (Val-A) is produced by Streptomyces as a secondary metabolite with wide agricultural applications of controlling rice sheath blight, false smut and damping-off diseases. The effect of alkaline pH shock on enhancing Val-A production and its mechanism were investigated. A higher yield of Val-A was achieved by NaOH shock once or several times together with faster protein synthesis and sugar consumption and alkaline pH shock can increase Val-A production by 27.43%. Transcription of genes related to amino acid metabolism, carbon metabolism and electron respiratory chain was significantly up-regulated, accompanied by the substantial increase of respiratory activity and glutamate concentration. Val-A production was promoted by a series of complex mechanisms and made a response to pH stress signal, which led to the enhancement of glutamate metabolism and respiration activity. The obtained information will facilitate future studies for antibiotic yield improvement and the deep revealment of molecular mechanism.